2021
DOI: 10.1061/(asce)cf.1943-5509.0001657
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Overdeformed Shield Tunnel Lining under Grouting Treatment: Field Experiment

Abstract: Shield tunnel structures are commonly found to be over-deformed in Eastern China soft ground due to adjacent engineering activities. Grouting treatment could serve as a viable solution to reduce the excessive diametrical expansion of tunnel linings actively. However, understanding the groutinginduced effects on adjacent tunnel structures remains preliminary due to the scarcity of welldocumented case histories. In this study, a field experiment was conducted to explore a shield metro tunnel's real performance d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…This section gives an overview of an example case of a shield metro tunnel that was affected by large-scale excavations in the soft soil area during the redevelopment of a city area in China, which was reported in detail in Han et al [15]. The twin tunnels were put into operation in 2010, and two years later, large excavations took place near the tunnels as part of the construction of 10 highrise towers (total basement area around 90,000 m 2 ).…”
Section: Metro Tunnel Structural Integrity: a Typical Case Of Over-de...mentioning
confidence: 99%
See 4 more Smart Citations
“…This section gives an overview of an example case of a shield metro tunnel that was affected by large-scale excavations in the soft soil area during the redevelopment of a city area in China, which was reported in detail in Han et al [15]. The twin tunnels were put into operation in 2010, and two years later, large excavations took place near the tunnels as part of the construction of 10 highrise towers (total basement area around 90,000 m 2 ).…”
Section: Metro Tunnel Structural Integrity: a Typical Case Of Over-de...mentioning
confidence: 99%
“…A recent study [15] reported a full-scale field experiment of grouting treatment in Eastern China soft ground in connection to a retrofitting operation to reduce the convergence of the tunnels under consideration. The effects of different routing arrangements and grouting history on the grouting efficiency, the timevarying response of the tunnel linings, and the characteristics of the tunnel lining rebounding after grouting, were examined.…”
Section: Typical Remedial Measures Against Over-deformed Tunnel Struc...mentioning
confidence: 99%
See 3 more Smart Citations